Risk factors for high-risk and multi-type Human Papillomavirus infections among women in Ho Chi Minh City, Vietnam: a cross-sectional study - Tran, Ly Thi-Hai (BMC Womens Health, 2015)
BACKGROUND: Concurrent infection with multiple types of Human Papillomavirus (HPV) is associated with an increased risk of cervical cancer; yet, little is known about risk factors for concurrent HPV infection in Vietnam. This study investigated the prevalence of and risk factors for high-risk-type HPV and multi-type HPV infections among women in Ho Chi Minh City, Vietnam. METHODS: Data were collected from a population-based survey of 1,550 women (mean age = 42.4; SD = 9.5), using a multi-stage sampling process. Socio-demographic and behavioral variables were obtained by self-report. HPV genotypes in cervical specimens were identified using PCR protocols. RESULTS: The prevalence of any high-risk HPV infection was 9.0%, and of multi-type HPV infection was 1.9%. In the HPV+ subsample, the percentage of high-risk HPV was 84% and of multi-type HPV was 20%. All multi-type HPV infections were high-risk-type. Lifetime smoking and older age of first sex were significantly associated with any high-risk and multi-type HPV infections. Regular condom use was inversely associated with high-risk and multi-type HPV infection. CONCLUSIONS: Risk factors for high-risk and multi-type HPV infections were similar. Further research and intervention are needed to reduce HPV infections in order to prevent HPV-related cancers.